Factors affecting groundnut output in Andhra Pradesh: co-integration and error-correction modeling: FACTORS AFFECTING GROUNDNUT OUTPUT IN ANDHRA PRADESH - ASHOK KUMAR; K N SINGH; S P BHARDWAJ (Journal of Oilseeds Research, 2014)
Groundnut is an important oilseed crop of India. The area under groundnut in India was maximum (8.0 million ha), however the production was less due to the lowest yield (938 kg/ha) among all Asian countries. Thus it becomes more important to identify the factors affecting groundnut productivity which is directly related to the farmer’s income, sustainable supply and the price stabilization. Unless until the factors affecting groundnut productivity are known, the corrective measures can not be initiated. In this paper efforts have been made to examine whether producer’s price, area cultivated, fertilizer applied and rainfall have an important effect on groundnut production in Andhra Pradesh using co-integration and error correction modeling. Co-integration and error correction modeling tend to solve spurious regression results obtained from the analysis of macro-economic data and also establish an equilibrium long-run relationship which enables one to carry out a valid inference of the explanatory variables that are responsible for affecting the output of the crop. A stationary test was performed which revealed only rainfall series was stationary at level, while other series become stationary at first differencing applying the unit root test. Johansen co-integration and error correction procedure was adopted which indicates the existence of five co-integrating vectors at 1% level of significance, hence rejecting the null hypothesis of no co-integrating vector. Further, a parsimonious error correction model was applied. The statistical significance of error correction model for groundnut validates the existence of an equilibrium relationship among the variables. The results, therefore, indicate the combined effect of area, fertilizer, rainfall and price jointly affect the output of groundnut in Andhra Pradesh. Therefore, a favorable price policy, assured irrigation and timely supply of fertilizers at remunerative price would help the farmers to allocate more area under groundnut. These measures are necessary to enhance the productivity as well as income of the farmers and also supply of groundnut in the benefit of consumers.